Leaf geometric morphometric analyses of Callicarpa and Geunsia (Lamiaceae) in the Malesian region - Jennifer Danila; GRECEBIO JONATHAN D. ALEJANDRO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Danila JS, Alejandro GJD. 2021. Leaf geometric morphometric analyses of Callicarpa and Geunsia (Lamiaceae) in the Malesian region. Biodiversitas 22: 4379-4390. Leaves are one of the most substantial organs of plants for it serves as a basis of species identification. Leaf morphology provides distinguishing features that help in the discrimination of plant species as well as investigation of leaf features among populations. This study aimed to investigate leaf shape variations between the two genera Geunsia Blume group and its closely related taxon, Callicarpa L. (Lamiaceae) using a landmark-based geometric morphometric method. The differences in the leaf shape among former members of Geunsia, namely C. apoensis, C. basilanensis, C. flavida, C. paloensis, C. pentandra, C. ramiflora, and C. surigaensis are also evaluated. Two primary landmarks and 14 semilandmarks were assigned in all samples to represent changes around the leaf margin. The Procrustes fit was generated using MorphoJ software which displays the mean and landmark position for individual configurations. Canonical Variate Analysis (CVA) and Mahalanobis Distance (MD) were able to discriminate all samples of Geunsia species using a scatter plot. Furthermore, Procrustes ANOVA showed a significant difference (P = 0.0082) among the seven species of the Geunsia group. Based on the results obtained, geometric morphometrics of leaf shape is effective in interspecific discrimination within members of Geunsia. However, the result of Discriminant Analysis (DA) showed that Geunsia and Callicarpa groups made leaf shape differences inefficient in discriminating the two genera. Therefore, further morphological studies on landmark-based geometric morphometrics of leaf shape involving a larger number of samples especially in the study of intergeneric classification are suggested.